Employability of Latin honor graduate in a state university in the Philippines - Rico-Villanueva, Emelyn; Falo, Kim Jemar F.; Fampo-Ida, Annabelle; Punla, Ma. Levi R.; Sumanting, Rose L. (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examines the employability of Latin-honor graduates from Romblon State University (RSU) between 2015 and 2022, addressing the factors that influence their transition into the workforce. The research investigates how academic performance, board examination results, and advanced education impact employment outcomes. Using a mixed-method approach, including surveys and binary logistic regression analysis, the study identifies key predictors of employability. Results indicate that achieving academic honors, passing licensure exams, and pursuing further education significantly enhance graduates’ chances of securing permanent employment and advancing in their careers. These findings highlight the need for aligning RSU’s curriculum with labor market demands and underscore the importance of continuous professional development. The study offers practical recommendations to improve graduate employability and informs policy initiatives aimed at supporting career progression for Latin-honor graduates.